Nitrogen losses from soil as affected by water and fertilizer management under drip irrigation: Development, hotspots and future perspectives - Wei, Qi; Wei, Qi; Xu, Junzeng; Liu, Yuzhou; Wang, Dong; Chen, Shengyu; Qian, Wenhao; He, Min; Chen, Peng; Zhou, Xuanying; Qi, Zhiming (Agricultural water management, 2024)
While soil nitrogen (N) losses under drip irrigation water and fertilizer management have become a key issue in global environmental N pollution, no current systematic review of this issue exists in the literature. Drawn from the Web of Science Core Collection database, 290 related articles were identified as research subjects (1991–2022). To reveal the basic characteristics, research power, hotspots and future perspectives of this research field, an in-depth bibliometrics analysis and graphical knowledge display were undertaken by using CiteSpace software. By analyzing the evolution process of keywords, greenhouse gases, water use efficiency and crop yield have been research hotspots of this field in recent years. Irrigation systems, soil moisture, fertigation and N losses have always been the core research topics. The focus on N losses pathways has gradually shifted from nitrate (NO3-) leaching alone to comprehensive consideration of multiple losses pathways including NO3- leaching, and emissions of N2O, NH3 and NO. The corresponding water and fertilizer management strategies have gradually shifted from concentrating on water and fertilizer application amounts to diversified management methods involving combinations of amounts, methods and types. Moreover, the development and widespread application of new water and fertilizer management technologies and exogenous additives have further enriched the research direction of soil N losses under drip irrigation water and fertilizer management. Future research still needs to explore how to balance high crop yields and minimize environmental impacts, which will provide effective strategies for controlling agricultural non-point source pollution and mitigating global warming. [Display omitted] •Balancing high crop yields and environmental effects is the main issue.•Research topics shifted from NO3- leaching to multiple losses pathways.•Greenhouse gas emission, water use efficiency and crop yield are hotspots currently.